2016
DOI: 10.3844/ajassp.2016.697.707
|View full text |Cite
|
Sign up to set email alerts
|

Egg Consumption among Young People: A Study through the Application of the Logistic Regression Model

Abstract: The purpose of the present survey is to study and to investigate the proper eating style, focusing the attention on the propensity to "egg" consumption, in the diet of young people, with reference to the students attending the University of Messina. The data collection technique that was used consisted of the administration of a distributed anonymous ad hoc questionnaire by directly interviewing a sample of university students. In order to individualize the possible variables which may influence the frequency … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 30 publications
0
9
0
2
Order By: Relevance
“…The random search aimed at identifying the paramount factors, from which the consumer’s buying behavior is dictated (Lanfranchi et al , 2014). The questionnaire design led to the definition of the questions regarding the perceived quality, the usual consumption, the price-quality ratio of cow’s milk, non-cow’s milk and, more specifically, donkey milk (Lanfranchi et al , 2015; Giannetto et al, 2016; Chinnici, et al , 2002). The questionnaire wanted to report the perceived quality, the regular consumption, the price-quality ratio of the milk and more specifically of donkey milk.…”
Section: Methodsmentioning
confidence: 99%
“…The random search aimed at identifying the paramount factors, from which the consumer’s buying behavior is dictated (Lanfranchi et al , 2014). The questionnaire design led to the definition of the questions regarding the perceived quality, the usual consumption, the price-quality ratio of cow’s milk, non-cow’s milk and, more specifically, donkey milk (Lanfranchi et al , 2015; Giannetto et al, 2016; Chinnici, et al , 2002). The questionnaire wanted to report the perceived quality, the regular consumption, the price-quality ratio of the milk and more specifically of donkey milk.…”
Section: Methodsmentioning
confidence: 99%
“…Mizrak et al, (2012) indicated that for the Turkish consumer factors of purchasing were brand (13.29%), colour (4.33%), size (10.74%), date of production (62.40%), price (4.96%) and other (4.28%). In another study, 61% of university students indicated that price was the most effective factor on egg purchases, while 27% of students did not agree (Giannetto et al, 2016). Figure 4c showed the resources that the respondents used to obtain information about egg.…”
Section: Resultsmentioning
confidence: 96%
“…In the same study reported that similar to our findings, the age was more effective on egg consumption than other demographic data and 47.6% of the respondents liked eggs from locally-bred chicken (Ayim-Akonor and Akonor, 2014). In a recent study it was reported that the egg consumption frequency of age of under 21 was everyday (3.10%), 3-5 times (22.90%), 1-2 times (64.60%) and never (9.40%) (Giannetto et al, 2016). In the same study, the researchers reported the egg consumption frequency for consumers of age of 25 was everyday (2.40%), 3-5 times (18.30%), 1-2 times (68.30%) and never (11.00%) (Giannetto et al, 2016).…”
Section: Resultsmentioning
confidence: 98%
“…Ayim-Akonor & Akonor (2014) en un estudio similar, constatan que los más jóvenes presentan mayor probabilidad de consumir más huevos que los más adultos, mientras, Giannetto et al (2016) constatan que el 64,5% de los jóvenes entrevistados declaran un consumo de aproximadamente dos huevos por semana. Así mismo, Conrad et al (2017) constatan aumento en el consumo de huevo en período de 12 años (2001 -2002 y 2011 -2012) entre personas adultos norte-americanos, destacándose que los beneficios nutricionales, así como su bajo costo y versatilidad culinaria son los factores principales por el cual consumen el huevo.…”
Section: Resultados Y Discusiónunclassified